2014
DOI: 10.1038/nature13917
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing identifies rare LDLR and APOA5 alleles conferring risk for myocardial infarction

Abstract: Summary Myocardial infarction (MI), a leading cause of death around the world, displays a complex pattern of inheritance1,2. When MI occurs early in life, the role of inheritance is substantially greater1. Previously, rare mutations in low-density lipoprotein (LDL) genes have been shown to contribute to MI risk in individual families3–8 whereas common variants at more than 45 loci have been associated with MI risk in the population9–15. Here, we evaluate the contribution of rare mutations to MI risk in the pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
458
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 590 publications
(488 citation statements)
references
References 49 publications
25
458
1
4
Order By: Relevance
“…This becomes even more apparent since we also detected a missense variant in the LPL gene, which led to a 20% reduction in LPL activity, to be associated with increased risk for CAD (Stitziel et al , 2016). The findings for LPL and ANGPTL4 confirm recent results for two other regulators of LPL activity, APOA5 and APOC3, in that rare APOA5 mutations increase both plasma triglyceride levels and risk of CAD (Do et al , 2015), whereas rare loss‐of‐function mutations in the APOC3 gene have opposite effects (The TG and HDL Working Group of the Exome Sequencing Project, National Heart, Lung, and Blood Institute, 2014). Taken together, LPL activity seems to have a central role in triglyceride metabolism (Fig 3A) and consecutively CAD risk (Fig 4).…”
Section: Triglyceride Metabolismsupporting
confidence: 82%
“…This becomes even more apparent since we also detected a missense variant in the LPL gene, which led to a 20% reduction in LPL activity, to be associated with increased risk for CAD (Stitziel et al , 2016). The findings for LPL and ANGPTL4 confirm recent results for two other regulators of LPL activity, APOA5 and APOC3, in that rare APOA5 mutations increase both plasma triglyceride levels and risk of CAD (Do et al , 2015), whereas rare loss‐of‐function mutations in the APOC3 gene have opposite effects (The TG and HDL Working Group of the Exome Sequencing Project, National Heart, Lung, and Blood Institute, 2014). Taken together, LPL activity seems to have a central role in triglyceride metabolism (Fig 3A) and consecutively CAD risk (Fig 4).…”
Section: Triglyceride Metabolismsupporting
confidence: 82%
“…1 Recently, there has been a deepening interest in evaluating the extent to which rare variants contribute to variation in complex traits and diseases. [2][3][4][5][6][7][8][9] This has motivated development of statistical methods for testing rare-variant associations at the gene level. [10][11][12][13][14][15][16] Although these methods are useful for increasing statistical power to detect associations relative to single-variant analyses, valid well-powered statistical analyses are contingent on careful examination of phenotypes and underlying assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies have shown that elevated triglycerides correlate with elevated cardiovascular risk,4, 5 and the American Heart Association has long recognized that elevated triglycerides are an important marker of cardiovascular risk 6. More recently, genetic,7, 8, 9, 10, 11, 12, 13 genome‐wide analysis,14, 15, 16, 17 and mendelian randomization18, 19, 20, 21, 22 studies have suggested a causal role for triglycerides as a modifiable risk factor in the development and progression of ASCVD. Analyses from clinical data have demonstrated that lower on‐treatment triglycerides correlate with reduced cardiovascular risk 23, 24…”
mentioning
confidence: 99%